Perspektif Ekologi Politik Kebijakan Pengelolaan Danau Limboto - Hasim Hasim (Universitas Muhammadiyah Gorontalo, 2018)
The Limboto Lake is the largest lake in Gorontalo Province. These natural resources have biodiversity of fishery which become economic source of coastal lake community. Besides, the economic activity of aquaculture fishery also grows rapidly in Limboto lake. The Limboto Lake is the largest lake in Gorontalo Province. These natural resources have biodiversity of fishery which become economic source of coastal lake community. Besides, the economic activity of aquaculture fishery also grows rapidly in Limboto lake ,The Limboto Lake has a strategic role for the province of Gorontalo. The Limboto lake degradation shows a more destructive of the area and the depth is reduced. This research study the product of law as a environmental politic instrument of the government and analyzes it in a political ecological perspective. The research design used descriptive quantitative and qualitative by using methodological approach of political ecology. The results show that regulation related to general management of the lake and Lake Limboto is particularly weak in the context of cohesiveness, harmonization, and problem focus. Danau Limboto merupakan danau terbesar di Provinsi Gorontalo. Sumberdaya alam ini memiliki kakayaan hayati perikanan yang menjadi sumber ekonomi masyarakat pesisir danau. Disamping itu aktivitas ekonomi perikanan budidaya juga tumbuh pesat di danau Limboto. Danau Limboto merupakan danau terbesar di Provinsi Gorontalo. Sumberdaya alam ini memiliki kakayaan hayati perikanan yang menjadi sumber ekonomi masyarakat pesisir danau. Disamping itu aktivitas ekonomi perikanan budidaya juga tumbuh pesat di danau Limnboto. Danau Limboto memiliki peran strategis bagi provinsi Gorontalo. Degrdasi danau Limboto menunjukkan gambaran semakin destruktif yaitu luasan dan kedalamannya berkurang. Penelitian ini bertujuan untuk mengkaji produks hukum sebagai instrumen politik lingkungan pemerintah dan menganalisis dalam perspektif ekologi politik. Desain penelitian yang digunakan deskriptif kuantitatif dan kualitatif dengan menggunakan pendekatan metodelogis ekologi politik. Hasil menunjukkan bahwa regulasi terkait pengelolaan dananu secara umum dan danau Limboto secara khusus masih lemah dalam konteks keterpaduan, harmonisasi, dan fokus masalah.